2023
DOI: 10.1039/d3py00144j
|View full text |Cite
|
Sign up to set email alerts
|

3D printing soluble solids via PISA

Abstract: Polymer-Induced Self Assembly (PISA) is a technique that often involves the use of a macro-chain transfer agent (macro-CTA) polymerized through reversible addition-fragmentation chain transfer (RAFT), which is then chain extended...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The goals of this study were 3-fold: first, to assess the ability to create high-resolution objects using the PISA printing method; second, to confirm that these objects are not cross-linked and can dissolve in suitable solvents; and third, to create resin mixtures that print well in organic solvents such as isopropanol but can also dissolve at controlled rates under physiological conditions. In our previous PISA printing study, we found that the use of macro-CTAs with multiple RAFT CTAs is crucial for achieving the mechanical strength necessary to PISA print objects with a DLP printer . We hypothesize that the mechanical stability of the printed objects arises from a combination of interparticle bridging and knotting among the soluble corona-stabilizing segments (Figure A,B).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The goals of this study were 3-fold: first, to assess the ability to create high-resolution objects using the PISA printing method; second, to confirm that these objects are not cross-linked and can dissolve in suitable solvents; and third, to create resin mixtures that print well in organic solvents such as isopropanol but can also dissolve at controlled rates under physiological conditions. In our previous PISA printing study, we found that the use of macro-CTAs with multiple RAFT CTAs is crucial for achieving the mechanical strength necessary to PISA print objects with a DLP printer . We hypothesize that the mechanical stability of the printed objects arises from a combination of interparticle bridging and knotting among the soluble corona-stabilizing segments (Figure A,B).…”
Section: Introductionmentioning
confidence: 95%
“…In our previous PISA printing study, we found that the use of macro-CTAs with multiple RAFT CTAs is crucial for achieving the mechanical strength necessary to PISA print objects with a DLP printer. 17 We hypothesize that the mechanical stability of the printed objects arises from a combination of interparticle bridging and knotting among the soluble corona-stabilizing segments (Figure 1A,B). To prepare macro-CTAs with multiple covalently bound CTAs, we first homopolymerized a RAFT transmer to produce a highly branched polymer.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our initial work on RAFT PISA printing utilized a difunctional poly(ethylene glycol) (PEG) macro-CTA, chain extended with diacetone acrylamide (DAAm) in water, and 3D printed via DLP using lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) as a photo-initiator and phenol red as a photoabsorber. 29 In this study, we observed the dissolution behavior of DAAm PISA frogs in N , N -dimethylformamide (DMF), noting that those without N ′ N -methylene bisacrylamide (MBAc) crosslinker dissolved completely, indicating the presence of physical crosslinks. Building on this foundation, our second PISA printing study aimed to develop formulations capable of dissolving in physiological fluids with controlled kinetics.…”
Section: Introductionmentioning
confidence: 95%